Identification of candidate genes carrying polymorphisms associated with the risk of colorectal cancer by analyzing the colorectal mutome and microRNAome - Landi, Debora; Gemignani, Federica; Pardini, Barbara; Naccarati, Alessio; Garritano, Sonia; Vodicka, Pavel; Vodickova, Ludmila; Canzian, Federico; Novotny, Jan; Barale, Roberto; Landi, Stefano (Cancer, 2012)
BACKGROUND: The presence of single-nucleotide polymorphisms (SNPs) within the 3'-untranslated regions of genes could affect the binding between a microRNA (miRNA) and its target, with consequences on gene expression regulation. Considering the important role of miRNAs in carcinogenesis, it is hypothesized here that these SNPs could also affect the individual risk of colorectal cancer (CRC). METHODS: To test this hypothesis, a list was developed of 140 somatically mutated genes deduced from previous works on the mutome of the CRC. A further selection was conducted of SNPs within target sites for miRNAs that are expressed only in the colorectum (the colorectal microRNAome) and having adequate population frequencies. This yielded 12 SNPs that were genotyped in a case-control association study on 717 colorectal cases and 1171 controls from the Czech Republic. RESULTS: Statistically significant associations were found between the risk of CRC and the variant alleles of KIAA0182 (rs709805) (odds ratio = 1.57; 95% confidence interval = 1.06-2.78, for the variant homozygotes) and NUP210 genes (rs354476) (odds ratio = 1.36; 95% confidence interval = 1.02-1.82, for the variant homozygotes). CONCLUSIONS: The results support the study hypothesis and highlight the importance of SNPs within miRNA-dependent regulatory regions. Further studies on the role exerted by NUP210 and KIAA0182 in colorectal carcinogenesis are warranted.
Keywords: Linkage Disequilibrium; logistické modely; Polymorphism, Single Nucleotide; haplotypy; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; MicroRNAs; Multivariate Analysis; jednonukleotidový polymorfismus; Female; mutace; rizikové faktory; dospělí; Aged; Haplotypes; senioři; lidé; Genotype; Adult; ženské pohlaví; multivariační analýza; kolorektální nádory; Male; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; vazebná nerovnováha; Czech Republic; Odds Ratio; genotyp; mikro RNA; Risk Assessment; Mutation; Česká republika; mužské pohlaví; odds ratio; hodnocení rizik; Logistic Models; Colorectal Neoplasms; Risk Factors